Acute appendicitis in the third trimester of a pregnancy finished with spontaneous vaginal delivery - Milkovski, Daniel; Georgievska, Jadranka; Jovanovska, Viktorija; Simeonova, Slagjana; Aluloski, Igor; Samardjiski, Igor; Ognenovic, Ljubo; Kjaev, Ivo; Joksimovic, Vladimir; Mida, Isa (Asclepius, 2018)
Acute appendicitis is the most common surgical problem occurring during pregnancy. Its incidence is more common in the second trimester and is confirmed in 1/1000 pregnancies. Clinical manifestations of acute appendicitis in pregnant patients are generally very similar to non- pregnant patients. We present, here, the case of a 29-year-old pregnant patient at 35+4 weeks of gestation with the signs of acute appendicitis. The patient underwent a successful open appendectomy of her perforated appendix, without performing a cesarean section (CS) at the same time. 5 weeks postoperatively, at term, labor was induced with vaginal prostaglandins and the patient delivered a healthy female baby without any complications. Immediate diagnosis of acute appendicitis during pregnancy is recommended and management with the suitable surgical intervention should not be delayed for >24 h as it increases the risk of perforation with its subsequent critical complications. The treatment of acute appendicitis is always surgical, with an appendectomy and perioperative broad-spectrum antibiotics. Except in cases of high maternal and fetal mortality, a CS should not be done simultaneously with the appendectomy in cases of a perforated appendix with diffuse peritonitis, due to the very high risk of dehiscence of the uterus.
Keywords: appendectomy; cesarean section; diffuse peritonitis; pregnancy; third trimester